Neutron research of the structure transition micelle to crystallites in liquid system D2O-tetradecyltrimethilammonium bromide-NaBr - L. A. Bulavin; O. I. Ivankov; V. M. Sysoev (Ядерна фізика та енергетика)
Structure transition in triple liquid system D2O-tetradecyltrimethilammonium bromide-NaBr was studied by means of small-angle neutron scattering in a wide range of temperature, pressure and salt concentrations. The phase P-T transition diagrams of colloidal micellar system to the suspension colloidal system with crystallites was construct from experimental data. It is shown that salt concentration increasing causes the shift of the boundary in the direction of higher temperatures and lower pressures. Thermodynamic justification of the received results is represented.